“We shouldn't encourage drug use”: Unpacking correctional officer opposition and support of the Prison Needle Exchange Program - Cindy Whitten; Rosemary Ricciardelli; Matthew S. Johnston (Social Sciences and Humanities Open, 2023)
Background: The Prison Needle Exchange Program (PNEP) is a harm reduction initiative which involves providing people who are incarcerated (PWAI) with sterile injection equipment to avoid harms associated with unsterilized needle use, such as the spread of infectious diseases. While current evidence strongly supports the implementation and monitoring of PNEP, the program's success requires institutional support along with staff and prisoner commitment. Methods: The current study draws on interview data to examine policies surrounding PNEP and correctional officers’ (COs) (n = 134) perceptions and attitudes toward PNEP. Results: The COs in our sample were strongly in opposition to PNEP, with only a handful supporting PNEP. Emergent themes underpinning their opposition related to a sense of injustice and an inherent tension between introducing needles into the prison versus how they understand their occupational role and responsibilities. Conclusion: We conclude with a discussion of policy recommendations aimed at implementing PNEP collaboratively with staff to ensure the benefits of harm reduction are fostered and realized.